PENGARUH TRISILA TNI AL TERHADAP PEMBENTUKAN SUMBER DAYA MANUSIA UNGGUL PRAJURIT DINAS PEMELIHARAAN DAN PERBAIKAN KAPAL KOMANDO ARMADA II - Teguh Setiyawan; Yohanes (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
Along with the development of science and technology that has led to glob-alization, the relevance of the Indonesian Navy Trisila is again tested in encour-aging the formation of excellent human resources (HR) for its soldiers. This study aims to analyze the influence of Military Discipline, Hierarchy and Hon-or as elements in the TNI AL Trisila on the formation of superior human re-sources for Satker "A" Koarmada soldiers. The sample used in this study were all soldiers of Satker "A" Koarmada totalling 70 personnel. Data collection was carried out using a questionnaire. The data was then tested using the multiple linear regression method partially and simultaneously using SPSS 25 for Window Software. The results showed that there was influence of 80,7%Trisila TNI AL as a independence variable towards on the formation of superior human re-sources for Repair and Maintenance Service of 2nd Fleet Command soldiers as a dependence variable which means that the influence given is positive, powerful, and significant.